2006
DOI: 10.1007/s10508-006-8995-9
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Self-Reported Sexual Orientation and Behavior in a Sample of Middle-Aged Male Injection Drug Users

Abstract: Data are sparse on injection drug using (IDU) men who have sex with men (MSM). Previous literature suggests perceived taboos can result in an underreporting of atypical sexual orientation (i.e., bisexuality, homosexuality). As a result, HIV prevention programs have been difficult to mount, particularly programs for IDU-MSM. The association between self-reported sexual orientation and sexual behavior at semi-annual study visits was longitudinally assessed in a population of 1300 male IDUs in Baltimore during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Consistent with previous research, participants inconsistently reported their sexual orientation/identity and sexual behavior (Washington et al, 2006). Hence, Web-based prevention programs are needed that include language specific to IDU-MSM/W, whose desire for money to purchase drugs may override their sexual preference.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Consistent with previous research, participants inconsistently reported their sexual orientation/identity and sexual behavior (Washington et al, 2006). Hence, Web-based prevention programs are needed that include language specific to IDU-MSM/W, whose desire for money to purchase drugs may override their sexual preference.…”
Section: Discussionsupporting
confidence: 59%
“…Many studies of HIV infection that included injection drug users (IDUs), since 1991, have focused on whether injection or sexual risk factors, or both, were associated with HIV seroconversion, and have not included STDs Kral, Bluthenthal, Lorvick, & Gee, 2001;Longshore, Bluthenthal, & Stein, 2001). Others have examined risk factors among IDUs (Kral, Bluthenthal, Erringer, Lorvick, & Edlin, 1999;McFarland, Kellog, Dilley, & Katz, 1997;Dushay, Singer, Weeks, Rohena, & Gruber, 2001), and explored the relationship between self-reported sexual orientation and behavior among IDUs (Pathela et al, 2006;Washington et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Interventions for non-identifying MSM may benefit from addressing community norms, sexual identity, and stigma as underlying factors that contribute to drug use and sexual risk behaviors 21. Interventions for bisexual and non-identifying MSM-IDUs should consider race/ethnicity as well as social and contextual factors, such as internalized homophobia and fear of disclosure 22.…”
Section: Men Who Have Sex With Men (Msm)mentioning
confidence: 99%
“…Moreover, the timeframe used for data collection will affect the classifications and potentially the results. Although some studies used relatively short times frames (3-6 months) to assess sexual behavior (Gorbach et al, 2009;Knight et al, 2007;Washington, Galai, & Cohn, 2006;Wheeler et al, 2008;Zule et al, 2009), larger population-based data sets tended to assess sexual behavior over the past year (Jeffries & Dodge, 2007;Koh & Ross, 2006;Spikes et al, 2009;Tao, 2008), 5 years (Midanik et al, 2007), or lifetime (Bostwick et al, 2010;Cochran & Mays, 2007;Koh & Ross, 2006;Levin et al, 2009;Pathela & Schillinger, 2010;Zellner, Marinez-Donate, & Sanudo, 2009).…”
Section: Introductionmentioning
confidence: 99%